Community intervention program. Domestic violence against women - Quiñones García, Iris; Valido Valdes, Doraimys (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Violence against women is an obstacle to achieving equality, equity, development, peace and social participation. It is multidimensional so its response must be global, systemic and holistic from prevention, assistance and protection to recovery. A descriptive, prospective, cross-sectional research was designed in the period from January to December 2023, in Villa 1 Popular Zone, in Consolation del Sur Municipality, Pinar del Río Province, where a group of women victims has been identified of domestic violence. The general objective was aimed at analyzing the perception that women who are victims of domestic violence have about the suffered violence. The population was made up of 40 women who demanded specialized care, to which an anonymous psychosocial survey was applied. Data analysis was performed using the SPSS statistical package. Outstanding results were obtained such as: in the studied women, young adults predominated, with partners, a high level of education, with or without a work relationship, from the urban area, the nuclear family predominated, being the aggressor the current partner, jealousy was the cause of abuse and its obvious link to alcohol. The most frequent type of violence was psychological or emotional. It reacts with more violence in the response of the victims, it was related to ingestion of alcoholic beverages and they told her that they should report and seek help. A Community Intervention Program is proposed.